Pengaruh Content terhadap Minat Beli dan Loyalitas Konsumen pada Produk Fashion dengan Influencer Sebagai Mediasi pada Shopee - Tarigan, Arihta; Lumika, Caroline Ketty (Universitas Batanghari, 2024)
This research was conducted to see the influence of content marketing in attracting customers in attracting customers in purchasing intention and consumer loyalty to fashion products. Looking at the phenomenon of influencer that have penetrated in digital media as well as its role in delivering content, this research will look at whether creative content, innovative content and interactive content have an influence on purchasing intention and consumer loyalty mediated by Influencer. This research uses quantitative methods with descriptive approaches and data collection using questionnaires with Google Forms. The results of this research show that creative content has a significant effect on influencers, innovative content has a significant effect on influencer, interactive content has no significant effect on influencer, influencer have a significant effect on purchase intention, and purchase intention has a significant effect on consumer loyalty. Indirectly, creative, innovative and interactive content has a significant effect on purchasing intention through influencer as mediation. Creative and interactive content has no significant effect on consumer purchase intention and consumer loyalty through influencer as mediation, and innovative content has a significant effect on consumer purchase intention and consumer loyalty through influencer as mediation.